DEMOCRATIC ESTABLISHMENT OF REGIONAL LAW REGULATIONS - Sumiaty Adelina Hutabarat (SEAN Institute, 2022)
Regional legal products in the form of decisions and regulations of regional governments can be caught as legal products that are legally flawed, although each formation of regional laws and regulations must always pay attention to the concept of the rule of law, the principle of democracy in the development of legislation. Based on research, the existence of regional laws and regulations made by local governments are in accordance with good legal principles, in accordance with Law Number 10 of 2004 concerning statutory regulations. The principle of democracy has been applied in the formation of regional legal arrangements with regional heads contained in the draft blood regulations that are proposed to come from the regional government and the DPRD for an integrated and systematic planning process for legislation and regulations.